Correlation study towards economic sufficiency indices among PLM Business School community households - Jeremy Ira T. Amarante, Denmark Belchez, Kiara Marie M. Brillo, Mariam R. Dilangalen, Eric Yancy O. Estrabo, Juliah Neil G. Pama, Bryan Dave Sodsod, Rowena T. Terrenal, Sophia Margareth S. Tonido, Karen M. Zambrana 4 0 16; 5
u
Business Research: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2021
Keywords: 2 -- 0; 6; 20; 20; 2